CULTURAL ADAPTATION AND CONTENT VALIDITY OF MEDICAL ADHESIVE-RELATED SKIN INJURY FOR PORTUGUESE IN BRAZIL (Estima – Brazilian Journal of Enterostomal Therapy, 2023)
Objective: To culturally adapt the Medical Adhesive Related Skin Injury (MARSI) classification instrument to the Brazilian Portuguese and test the content validity of the adapted version. Method: Three phases comprised the cultural adaptation: translation, evaluation by a committee of judges composed of ten stomal therapists and back-translation. The project was approved by the Research Ethics Committee of the University of São Paulo. Results: A Portuguese version of the instrument was obtained after translation, which was guided by the Likert scale. The controversial and divergent terms were discussed by the committee of judges and their content was validated in a focus group, generating a content validity index of 0.9. The version was back-translated and approved by one of the instrument’s developer, who just suggested an adaptation to the concept of allergic contact dermatitis. Conclusion: The translated and culturally adapted version of MARSI classification instrument was obtained and its content validity attested. Tests regarding inter- and intra-observer reliability and concurrent validity are needed.